PERSEPSI PERAWAT TERHADAP PRAKTIK KOLABORASI INTERPROFESIONAL DI RUANG INSTALASI GAWAT DARURAT KOTA SAMARINDA: THE RELATIONSHIP BETWEEN NURSES' PERCEPTION OF INTERPROFESSIONAL COLLABORATION PRACTICES IN THE EMERGENCY INSTALLATION ROOM OF SAMARINDA CITY - Jannah, Devita Nurul; Dwi Widyastuti; Milkhatun (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2024)
Introduction: The practice of interprofessional collaboration is a cooperative relationship between professions with the aim of making joint decisions to provide the best quality of service to patients. Differences in perception in health workers are an obstacle to the practice of interprofessional collaboration. The Emergency Installation Room (IGD) urgently needs collaborative practices because the Emergency Room is a service unit that pays attention to golden time so that it must have the right and fast service so that patients avoid disability and death. The purpose of this study is to determine the relationship between perception and interprofessional collaboration practices in the emergency department. Methods: The study uses a quantitative method with a cross sectional approach. The sampling used a total sampling with a sample of 54 respondents, data analysis using a descriptive statistical test and a Kendall Tau statistical test. Data collection used the Preception of Interprofessional Collaboration Model Questionaire (PINCOM-Q) and Collaborative Practice Assessment Tool (CPAT) questionnaires. Result: The study showed that the perception of nurses with the practice of interprofessional collaboration in the Emergency Installation room of Samarinda City was the same, namely the perception of good nurses 27 respondents (50.0%), and the perception of bad nurses 27 respondents (50.0%), as well as the practice of interprofessional collaboration was in line with the same between good and bad. The results of the bivariate test calculation using Kendall Tau obtained a correlation coefficient of 0.407 and a p value = 0.003, so that Ha was accepted. Conclusion: There is a relationship between nurses' perceptions and the practice of interprofessional collaboration in the emergency room. It is necessary to increase knowledge of collaborative practices in order to improve the perception of nurses, as well as clear policies and regulations in implementing interprofessional collaboration practices.